Physical and mechanical behavior of glulam beams produced with rubberwood treated with preservatives - Douglas Lamounier Faria; Thiago Moreira Cruz; Matheus Cordazzo Dias; Paulo Junio Duarte; Lourival Marin Mendes; José Benedito Guimarães Junior (Ciência e Agrotecnologia, 2020)
ABSTRACT This work aimed to evaluate the physical and mechanical behavior of glued laminated timber (GLT) - glulam pieces of Hevea brasiliensis treated with chromed copper arsenate (CCA), chromed copper borate (CCB) and pyrethroid in the production of GLT. The pieces were produced using three wooden laminae with dimensions of 60 x 20 x 1200 mm, (width x thickness x length), joined with epoxy adhesive under 1.0 MPa pressure for 24h at room temperature. The rubberwood had an apparent density of 0.624 g cm-3, a value close to that of Eucalyptus grandis wood, a species traditionally used in the manufacture of GLT. Regarding the GLT parts, it was observed that the preservative treatment with CCA and CCB influenced negatively the values of the mechanical properties. For resistance modulus (MOR), a reduction of 75.44 MPa to 62.36 and 58.57 MPa was found for the parts untreated and treated with CCA and CCB, respectively. There was no statistical difference for surface treatment with pyrethroid. The photomicrographs of the glue line showed that the reduction in these values was mainly due to the penetration of preservative solutions into the wood structure (cell lumens and vessels or pores), impairing the anchoring of the adhesive.